Effects of Sacubitril/Valsartan in the PARADIGM-HF Trial (Prospective Comparison of ARNI with ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure) According to Background Therapy. (September 2016) - Okumura, Naoki; Jhund, Pardeep S.; Gong, Jianjian; Lefkowitz, Martin P.; Rizkala, Adel R.; Rouleau, Jean L.; Shi, Victor C.; Swedberg, Karl; Zile, Michael R.; Solomon, Scott D.; Packer, Milton; McMurray, John J.V.
Abstract : Background—: In the PARADIGM-HF trial (Prospective Comparison of ARNI with ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure), the angiotensin receptor neprilysin inhibitor sacubitril/valsartan was more effective than the angiotensin-converting enzyme inhibitor enalapril in patients with heart failure and reduced ejection fraction. We examined whether this benefit was consistent irrespective of background therapy. Methods and Results—: We examined the effect of study treatment in the following subgroups: diuretics (yes/no), digitalis glycoside (yes/no), mineralocorticoid receptor antagonist (yes/no), and defibrillating device (implanted defibrillating device, yes/no). We also examined the effect of study drug according to β-blocker dose (≥50% and <50% of target dose) and according to whether patients had undergone previous coronary revascularization. We analyzed the primary composite end point of cardiovascular death or heart failure hospitalization, as well as cardiovascular death. Most randomized patients (n=8399) were treated with a diuretic (80%) and β-blocker (93%); 47% of those taking a β-blocker were treated with ≥50% of the recommended dose. In addition, 4671 (56%) were treated with a mineralocorticoid receptor antagonist, 2539 (30%) with digoxin, and 1243 (15%) had a defibrillating device; 2640 (31%) had undergone coronary revascularization. Overall, the sacubitril/valsartan versus enalapril hazard ratio for the primary composite end point was 0.80 (95% confidence interval, 0.73–0.87; P <0.001) and for cardiovascular death was 0.80 (0.71–0.89; P <0.001). The effect of sacubitril/valsartan was consistent across all subgroups examined. The hazard ratio for primary end point ranged from 0.74 to 0.85 and for cardiovascular death ranged from 0.75 to 0.89, with no treatment-by-subgroup interaction. Conclusions—: The benefit of sacubitril/valsartan, over an angiotensin-converting enzyme inhibitor, was consistent regardless of background therapy and irrespective of previous coronary revascularization or β-blocker dose. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01035255. Abstract : Supplemental Digital Content is available in the text.